Integrated approaches to howler monkey (Alouatta spp.) medicine in professional care and conservation - Yarto-Jaramillo, Enrique; Çitaku, Irindi; Rodríguez, Carlos Enrique; Lewy Sánchez-Aldana, Claudia; Morales, Mary Carmen; Moresco, Anneke (Frontiers in Veterinary Science, 2022)
Howler monkeys (Alouatta spp.) are threatened by anthropogenic pressures such as habitat fragmentation and deforestation, while conservation efforts are challenging to coordinate as natural geographic distribution ranges are the largest of any New World primate. On a One Health front, howler monkeys represent a great model to investigate the infectious disease dynamics between wild primates and humans as several infectious diseases affecting howlers have a demonstrated zoonotic potential. Howler monkey populations in professional care offer a window to investigate susceptibility to diseases in this species such as yellow fever (YF) and malaria, plus a myriad of endoparasite phyla, as well as vector-borne diseases such as Chagas disease and leishmaniasis. More studies are urgently needed to provide species-specific, medically relevant information as well as clinical descriptions of animals considered medically healthy. Moreover, howler monkeys are a challenging species to breed and maintain in professional care; additionally, reproductive parameters have been published only for a handful of species in this genus. On a One Health approach communication and collaborative health surveillance involving wildlife and zoo experts will ease the identification of factors that contribute to disease emergence facilitating the integration of human, animal, and environmental health. The One Welfare concept is based on the inextricable connection among animal welfare, human welfare, and environmental conservation. Integrating One Health and One Welfare into actions both in-situ and ex-situ will promote the sustainability of the forests and restoration of the ecosystems that those species inhabit, transitioning to a comprehensive One Conservation approach.